Proton-boron capture interaction enhances killing of radiation resistant cancer cells - Pang, Dalong; Jung, Mira; Velena, Alfredo; Parke, William; Dritschilo, Anatoly (Frontiers in Oncology, 2025)
Background/objectivesStudies involving the interaction of protons with boron (11B) have shown potential for enhanced cell killing in cancer cells. However, theoretical analyses conducted using Monte Carlo simulations have not corroborated the experimental findings. Our objective is to independently investigate the effects of proton-boron capture interaction on the killing of cancer cells in SQ20-B and MCF-7 cells.MethodsCell survival and DNA damage endpoints were analyzed in radiation resistant SQ-20B cells and in radiation sensitive MCF-7 cancer cells after exposure to 11B (BSH11) and proton irradiation. Clonogenic cell survival curves were assessed to fit the Linear Quadratic (LQ) and Single-Hit Multi-Target (SHMT) models. Additionally, γH2AX foci were quantified to evaluate DNA damage up to 24 hours post irradiation, comparing the effects of proton irradiation alone to proton irradiation in the presence of boron in SQ-20B cells.ResultsExposure of cells to BSH11 resulted in decreased survival of SQ-20B cells following proton irradiation as compared to untreated control cells. Assays measuring γH2AX showed prolonged presence of γH2AX foci in cells after proton exposure in the presence of BSH11. In contrast, cells treated with BSH11 and irradiated with Cs-137 γ-rays did not show cell killing enhancement. Additionally, cells treated with BSH10, an analog of BSH11 that contains only 10B, displayed no change in survival after proton irradiation compared to untreated cells.ConclusionsOur data show a small enhancement of cell killing by proton radiation in the presence of BSH11 that we attribute to the proton-boron interaction. Analysis of γH2AX demonstrates a prolonged duration of foci formation in cells after proton irradiation in the presence of BSH11. Further research will be needed to better understand the potential clinical applications of proton-boron interaction.